Respuesta :
Answer:
A.-7
Step-by-step explanation:
If [tex]2x-3y=11[/tex] and [tex]3x+15=0[/tex]
To know the value of y we need to clear x in the equation [tex]3x+15=0[/tex] and the result replace it in [tex]2x-3y=11[/tex].
Then, let's clear x in the equation [tex]3x+15=0[/tex]
[tex]3x=-15\\x=-\frac{15}{3} =-5[/tex]
Substituting the value of x in the equation [tex]2x-3y=11[/tex]
[tex]2(-5)-3y=11\\-10-3y=11\\-3y=11+10\\y=\frac{11+10}{-3} \\y=\frac{21}{-3}\\ y=-7[/tex]
Answer:
a) y = -7.
Step-by-step explanation:
2x − 3y = 11
3x + 15 = 0
From the second equation:
3x = -15
x = -5.
Substitute this value in the first equation:
2(-5) - 3y = 11
-10 - 11 = 3y
3y = -21
y = -7.